REFORMASI HUKUM KEPAILITAN TERHADAP KOPERASI: PEMBATASAN PERMOHONAN PAILIT TERHADAP KOPERASI OLEH ANGGOTA - Avisena, Aditya Fadhil; Diza Liestiara, Dhea Ranissya (Jurnal Legislatif, 2023)
Bankruptcy petitions by cooperative members have increased since the Covid-19 pandemic. This phenomenon raises critics over the disregard for the principle of kinship and the urgency for the government to establish a medium that has the authority to file bankruptcy petitions against cooperatives. This research is structured with juridical-normative research methods along with conceptual approach. This research aims to provide solutions for the government in answering the current issue regarding cooperatives' bankruptcy petitions by its members. Cooperatives have become a place for society to save money, even in practice cooperatives are often used as a place to invest. In this regard, cooperatives are important entities to be maintained because their existence involves public interests. Thus, it is necessary to attribute authority to the Ministry of Cooperatives and Small and Medium Enterprises to become the medium in terms of filing bankruptcy petitions against cooperatives. The attribution should be contained in the law on bankruptcy and postponement of debt repayment obligations as well as the law on cooperatives which should be drafted in the future by the government together with the House of Representatives so that there is a guarantee of fresh air in the cooperative sector in Indonesia.